Stress distribution correlated with damage in duplex stainless steel studied by synchrotron diffraction during plastic necking. (5th January 2017) - Zhao, Y.; Le Joncour, L.; Baczmański, A.; Gadalińska, E.; Wroński, S.; Panicaud, B.; François, M.; Braham, C.; Buslaps, T.
Abstract: The goal of this work was the determination of lattice strains distribution in two phases of duplex steel during plastic necking. Subsequently, the stress heterogeneity in the neck was studied in order to determine the reason for the damage initiation and to verify the hypothesis that the damage begins in the ferritic phase. To do this, X-ray synchrotron radiation was used to scan the 'in situ' variation of the interplanar spacings along the necking zone for samples subjected to tensile loading. A self-consistent model and FEM simulation were applied for the experimental data interpretation. It was found that for advanced necking the phase lattice strains, especially those measured at some distance from the neck centre, show a large inversion of the loads localised in both phases compared to the undamaged state (the lattice strains in the ferrite become smaller than in the austenite). This effect indicates stress relaxation in the ferrite which is connected with the damage phenomenon. Correlation of the experimental results with the modelling shows that the value of von Mises stress is responsible for the initiation of the ferritic phase softening. Graphical abstract: Highlights: Relaxation of stress in ferrite indicates damage initiation in this phase for a large deformation of duplex steel. The stress relaxation in ferrite depends on the grain orientation and position in the neck. Heterogeneous lattice strains and three-axial heterogeneous stresses are present in the necking zone. The softening/damage process in ferrite depends on the value of equivalent von Mises stress.